Informed Consent Documents Used in Critical Care Trials Often Do Not Implement Recommendations*. Issue 2 (February 2018) - Atwere, Pearl; McIntyre, Lauralyn; Carroll, Kelly; Hayes, Tavis; Brehaut, Jamie C.
Abstract : Objective: Informed consent documents are often poorly understood by research participants. In critical care, issues such as time pressure, patient capacity, and surrogate decision making complicate the consent process further. Recommendations exist for addressing critical care–specific consent issues; we examined how well existing practice implements these recommendations. Design: We conducted a systematic search of the literature for recommendations specific to critical care informed consent and rated existing informed consent documents on their implementation of 1) 18 of these critical care recommendations and 2) 36 previously developed general informed consent recommendations. Four hundred twelve registered critical care trials were identified and a request sent to the principal investigators for an example of the informed consent document associated with the trial. Each consent document was rated on both set of recommendations. Setting: We evaluated informed consent documents for trials conducted in English or French registered with clinicaltrials.gov. Patients: Not applicable. Interventions: Not applicable. Measurements and Main Results: Independent coders rated implementation of each recommendation on a four-point scale. Of 412 requests, 137 informed consent documents were returned, for a response rate of 34.1%. Of these, 86 met inclusion criteria and were assessed. Overall agreement between raters was 90.6% (weighted κ = 0.79; 0.77–0.81). Implementation of the 18 critical care recommendations was highly variable, ranging between 2% and 96.5%. Conclusions: Critical care studies often do not provide the information recommended for those providing consent for research. These clear recommendations provide testable hypotheses about how to improve the consent process for patients and family members considering trial participation in the critical care setting. Abstract : Supplemental Digital Content is available in the text.